Evaluation of rate-determining step of methane hydrate decomposition by measurement of transient heat and mass transfer near solid–gas interface. (March 2020) - Kanda, Yuki; Komatsu, Hiroyuki; Okajima, Junnosuke; Maruyama, Shigenao; Komiya, Atsuki
Highlights: We studied transient heat and mass transfer near methane hydrate interface. High-speed phase-shifting interferometer is used in the decomposition measurement. Temperature and concentration variations are evaluated by numerical simulations. Measurement results were verified by comparison with numerical simulation results. The dissociation phenomenon is estimated as the reaction rate-determining step. Abstract: The transient heat and mass transfer near a methane hydrate decomposition interface were quantitatively measured to evaluate the rate-determining factors of dissociation with high spatiotemporal resolution. In this study, we proposed a measurement system for the dissociation phenomenon near the hydrate interface, and the rate-determining step of the dissociation phenomenon was discussed in terms of the experimental results and numerical simulation using a dissociation model. The hydrate was generated around a water-like film under temperature of 274 K and pressure of 4.8 MPa of mixed gas comprising methane and helium in a temperature and pressure controlled system. A high-speed phase-shifting interferometer was used to measure the interfacial transient heat and mass transfer. In the present study, transient variations in the optical path length difference caused by the variation in the density field near the hydrate interface were visualized with temporal and spatial resolutions of 1 ms and 3.88 μm/pixel, respectively. The measured values were compared with the results of numerical simulations, assuming that the mass flux of methane was a function of the activation energy of dissociation. The comparison showed that the experimentally measured values exhibited similar tendency as the values estimated using the activation energy of approximately 60, 000 J/mol. This result was also confirmed from the interface shape variation of the hydrate. Finally, the dissociation phenomenon of the hydrate was estimated as the rate-determining step of the reaction by using our special interferometer system.